FACTORES NERVIOSOS EN EL SHOCK TRAUMATICO EXPERIMENTAL Y EFECTO DE LAS INYECCIONES INTRACISTERNALES DE POTASIO - OBRADOR ALCALDE, S; ARAICO REMUS, J (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1943)
Comparative study of the actions of papain and of mexicain on fibrinogen showed that electrolytes and amino-acids exerted a great influence in such actions The enzyme conc followed the equation 1/T = (E[long dash]c)k, which was the same for both trombin
BOL INST ESTUD MED BIOL
Keywords: FACTORES, NERVIOSOS, SHOCK, TRAUMATICO, EXPERIMENTAL, INYECCIONES, INTRACISTERNALES, POTASIO; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA